Correlation between platelet counts, MPV, PDW, PCT and age in acute ischemic stroke patients - Ebrahim Mohammed Abed Ahamid Ahmed; Babker Ahmed Mohamed; Bakri Yousf Mohamed Nour; Babiker Saad Almugadam (Medical Laboratory Journal)
Background: Acute ischemic stroke occurs when blood clots obstruct blood vessels within the brain. Platelets (Plts) are integral to the pathophysiology of stroke. This research aimed to explore the relationship between Plt quality and Plt indices in the context of acute ischemic stroke. Methods: This cross-sectional investigation involved 100 patients diagnosed with acute ischemic stroke at Kosti Teaching Hospital and Alyammama Hospitals. The diagnosis was confirmed using brain CT imaging and electrocardiography (ECG). Blood samples were collected in EDTA-containing tubes within 24 hours following the commencement of treatment and were subsequently analyzed for Plt count, mean Plt volume (MPV), Plt distribution width (PDW), and plateletcrit (PCT) utilizing a hematological analyzer. Data were analyzed using GraphPad Prism software. Results: Platelet counts negatively correlated with PDW [r=-0.074, P=0.459; R=-0.023, P=0.815], MPV [r=-0.130, P=0.194; R=-0.081, P=0.417], and diastolic blood pressure [r= -0.023, P=0.818; R= -0.024, P=0.805]; and positively correlated with PCT [r= 0.103, P=0.308; R=0.143, P=0.155] and diastolic blood pressure [r=0.022, P=0.823; R= 0.008, P=0.932]. Moreover, PDW positively correlated with systolic blood pressure [r=0.105, P=0.298; R= 0.147, P=0.148] and diastolic blood pressure [r=0.146, P=0.145; R=0.173, P=0.084]. Based on Spearman but not Pearson correlation, PDW showed a negative correlation with PCT [r=-0.005, P=0.959; R=0.010, P=0.929]. Conclusion: The study shows a correlation between Plt count and indices in ischemic stroke patients. The research also presented evidence concerning the relationship between diastolic and systolic blood pressure and Plt counts and indices.